2020
DOI: 10.3892/or.2020.7695
|View full text |Cite
|
Sign up to set email alerts
|

Sinoporphyrin sodium is a promising sensitizer for photodynamic and sonodynamic therapy in glioma

Abstract: The aim of the present study was to explore the antitumor effects of sinoporphyrin sodium (DVDMS)-mediated photodynamic therapy (PDT) and sonodynamic therapy (SDT) in glioma, and to reveal the underlying mechanisms. The uptake of DVDMS by U-118 MG cells was detected by flow cytometry (FCM). A 630-nm semiconductor laser and 1-MHz ultrasound were used to perform PDT and SDT, respectively. Cell proliferation and apoptosis were evaluated using the Cell Counting Kit-8 assay, FCM and Hoechst 33258 staining, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 50 publications
1
13
0
3
Order By: Relevance
“…SDT is a promising new option for the invasive treatment of tumors ( 62 ). SDT is similar to PDT in that it requires the combination of sensitizers, ultrasound and molecular oxygen ( 61 ).…”
Section: Biological Effects Of Bbr-mediated Pdtmentioning
confidence: 99%
“…SDT is a promising new option for the invasive treatment of tumors ( 62 ). SDT is similar to PDT in that it requires the combination of sensitizers, ultrasound and molecular oxygen ( 61 ).…”
Section: Biological Effects Of Bbr-mediated Pdtmentioning
confidence: 99%
“…Overall, four studies in vitro observed a selective accumulation of DVDMS compounds in glioma cells, which was generally superior in liposomal compounds than for the dye alone [ 71 , 72 , 73 , 74 ]. All studies reported higher rates of apoptosis, necrosis and growth inhibition in SDT schemes; sonication alone was inferior to sonodynamic therapy.…”
Section: Sonosensitizers For Brain Tumorsmentioning
confidence: 99%
“…All studies reported higher rates of apoptosis, necrosis and growth inhibition in SDT schemes; sonication alone was inferior to sonodynamic therapy. In vivo models, employing either subcutaneous grafts [ 71 , 73 , 74 ] or intracerebral inoculation [ 72 ] of glioma cells, highlighted that SDT granted a significant survival benefit in treated groups compared to both controls and subjects who were only sonicated. Moreover, histopathological analyses observed elevation of apoptosis markers; in particular, Wen An et al reported that both SDT and PDT reduced Bcl-x and p62 expression [ 74 ].…”
Section: Sonosensitizers For Brain Tumorsmentioning
confidence: 99%
See 2 more Smart Citations